Mice lacking the synaptic adhesion molecule Neph2/Kirrel3 display moderate hyperactivity and defective novel object preference - Choi, Su Yeon; Han, Kihoon; Cutforth, Tyler; Chung, Woosuk; Park, Haram; Lee, Dongsoo; Kim, Ryunhee; Kim, Myeong-Heui; Choi, Yeeun; Shen, Kang; Kim, Eunjoon (Frontiers in Cellular Neuroscience, 2015)
Synaptic adhesion molecules regulate diverse aspects of neuronal synapse development, including synapse specificity, formation, and maturation. Neph2, also known as Kirrel3, is an immunoglobulin superfamily adhesion molecule implicated in intellectual disability, neurocognitive delay associated with Jacobsen syndrome, and autism spectrum disorders. We here report mice lacking Neph2 (Neph2-/- mice) display moderate hyperactivity in a familiar, but not novel, environment and defective novel object recognition with normal performances in Morris water maze spatial learning and memory, contextual fear conditioning and extinction, and pattern separation tests. These mice also show normal levels of anxiety-like behaviors, social interaction, and repetitive behaviors. At the synapse level, Neph2-/- dentate gyrus granule cells exhibit unaltered dendritic spine density and spontaneous excitatory synaptic transmission. These results suggest that Neph2 is important for normal locomotor activity and object recognition memory.